Involving children and adolescents with type 1 diabetes in health care: a qualitative study of the use of patient-reported outcomes - Rikke Bjerre Lassen; Caroline Bruun Abild; Kurt Kristensen; Lene Juel Kristensen; Jens Thusgård Hørlück; Annesofie Lunde Jensen (SpringerOpen, 2023)
Abstract Background Within pediatric health care services, Patient-reported Outcomes (PROs) regarding the patient's health status are mainly used for research purposes in a chronic care setting. However, PROs are also applied in clinical settings in the routine care of children and adolescents with chronic health conditions. PROs have the potential to involve patients because they 'place the patient at the center' of his or her treatment. The investigation of how PROs are used in the treatment of children and adolescents and how this use can influence the involvement of these patients is still limited. The aim of this study was to investigate how children and adolescents with type 1 diabetes (T1D) experience the use of PROs in their treatment with a focus on the experience of involvement. Results Employing Interpretive Description, 20 semi-structured interviews were conducted with children and adolescents with T1D. The analysis revealed four themes related to the use of PROs: Making room for conversation, Applying PROs under the right circumstances, Questionnaire structure and content, and Becoming partners in health care. Conclusions The results clarify that, to some extent, PROs fulfill the potential they promise, including patient-centered communication, detection of unrecognized problems, a strengthened patient-clinician (and parent-clinician) partnership, and increased patient self-reflection. However, adjustments and improvements are needed if the potential of PROs is to be fully achieved in the treatment of children and adolescents.